The role of maternal homocysteine concentration in placenta-mediated complications: findings from the Ottawa and Kingston birth cohort - Chaudhry, Shazia H; Taljaard, Monica; MacFarlane, Amanda J; Gaudet, Laura M; Smith, Graeme N; Rodger, Marc; Rennicks White, Ruth; Walker, Mark C; Wen, Shi W (Université d'Ottawa | University of Ottawa, 2019)
Abstract Background Homocysteine is an intermediate metabolite implicated in the risk of placenta-mediated complications, including preeclampsia, placental abruption, fetal growth restriction, and pregnancy loss. Large cohort and case-control studies have reported inconsistent associations between homocysteine and these complications. The purpose of this study was to investigate whether elevated maternal plasma homocysteine concentration in the early to mid-second trimester is associated with an increased risk of placenta-mediated complications. We examined the following potential moderating factors that may explain discrepancies among previous studies: high-risk pregnancy and the MTHFR 677C>T polymorphism. Methods We analyzed data from participants recruited to the Ottawa and Kingston (OaK) Birth Cohort from 2002 to 2009 in Ottawa and Kingston, Canada. The primary outcome was a composite of any placenta-mediated complication, defined as a composite of small for gestational age (SGA) infant, preeclampsia, placental abruption, and pregnancy loss. Secondary outcomes were, individually: SGA infant, preeclampsia, placental abruption, and pregnancy loss. We conducted multivariable logistic regression analyses with homocysteine as the primary continuous exposure, adjusting for gestational age at the time of bloodwork and explanatory maternal characteristics. The functional form, i.e., the shape of the homocysteine association with the outcome was examined using restricted cubic splines and information criteria (Akaike’s/Bayesian Information Criterion statistics). Missing data were handled with multiple imputation. Results 7587 cohort participants were included in the study. Maternal plasma homocysteine concentration was significantly associated (linearly) with an increased risk of both the composite outcome of any placenta-mediated complication (p = 0.0007), SGA (p = 0.0010), severe SGA, and marginally with severe preeclampsia, but not preeclampsia, placental abruption and pregnancy loss. An increase in homocysteine concentration significantly increased the odds of any placenta-mediated complication (odds ratio (OR) for a 5 μmol/L increase: 1.63, 95% Confidence Interval (CI) 1.23–2.16) and SGA (OR 1.76, 95% CI 1.25–2.46). Subgroup analyses indicated some potential for modifying effects of the MTHFR 677C>T genotype and high-risk pregnancy, although the interaction was not statistically significant (high-risk subgroup OR 2.37, 95% CI 1.24–4.53, p-value for interaction =0.14). Conclusions Our results suggest an independent effect of early to mid-pregnancy elevated maternal homocysteine on placenta-mediated pregnancy complications.